Expressions of EZH2 and NOTCH3 pathway in osteosarcoma and their roles in osteosarcoma stem cells - Yan, Guangning; Lv, Yangfan; Lai, Xuwen; Li, Zhenlian; Ye, Danli; Wang, Wei; Qian, Yunfeng; Yu, Haojie; Wang, Zhuocai (Polish Journal of Pathology, 2022)
Osteosarcoma (OS) is the most common malignant bone tumour; however, the underlying mechanisms are mainly unknown. Enhancer of zeste homologue 2 (EZH2) and NOTCH pathway are important molecular signals related to carcinogenesis and tumour progression, but they are not fully understand in OS. Enhancer of zeste homologue 2, Notch3, HES1, and Nanog were detected on OS samples and statistically analysed. Expressions of these genes were investigate, and stem-like phenotype was verified in OS cells. This study found that higher EZH2 expression, Notch3 pathway, or Nanog were associated with tumour relapse and metastasis and a significantly shorter survival time. Moreover, the Notch3 pathway was activated in osteosarcoma stem cells. Enhancer of zeste homologue 2 overexpression could activate the Notch3 pathway and increase HES1 expression, leading to upregulated stem cell-related gene expression and self-renewal of OS cells. Our study demonstrates that EZH2, Notch3, and Nanog are important prognostic factors. Enhancer of zeste homologue 2 could maintain the self-renewal of OS cells, where the Notch3 pathway activation may be involved.